Effect of Garlic on Blood Pressure: A Meta‐Analysis. Issue 3 (5th January 2015) - Wang, Hai‐Peng; Yang, Jing; Qin, Li‐Qiang; Yang, Xiang‐Jun
<x xml:space="preserve">Abstract</x> Garlic supplements are thought to reduce blood pressure (BP). The authors performed a meta‐analysis to investigate garlic's effect on BP. Ovid Medline, Cochrane Library, and PubMed (1946 to November 2013) were used to search for randomized controlled trials. Seventeen trials were included. Pooled analysis showed that garlic intake caused a 3.75‐mm Hg reduction (95% confidence interval [CI], −5.04 to −2.45, I2=30.7%; P<.001) in systolic BP and a 3.39‐mm Hg reduction (95% CI, −4.14 to −2.65, I2=67%; P<.001) in diastolic BP compared with controls. Meta‐analysis of subgroups showed a significant reduction in systolic BP in hypertensive (−4.4 mm Hg; 95% CI, −7.37 to −1.42, I2=0.0%; P=.004) but not normotensive patients. No significant reduction in diastolic BP was seen. After sensitivity analysis, heterogeneity disappeared and significant diastolic BP reduction (−2.68 mm Hg, 95% CI, −4.93 to −0.42, I2=0.0%; P=.020) was shown in hypertensive patients. This meta‐analysis suggests that garlic supplements are superior to controls (placebo in most trails) in reducing BP, especially in hypertensive patients.